تقنيات الهاتف الحمول في المعاملات المالية المعاصرة " دراسة فقهية تحليلية" - Al Sakkaf Abdulrahman Saleh Abdulrahman
With the emergence of modern technology today, many issues emerged which require for light to be shed on, and to clarify the Islamic rulings regarding them. This includes mobile phone technologies used in modern financial transactions. The problem in this lies in the remarkable technological progress that mobile technology has achieved. These technologies have taken place of many classical methods, whether in buying, selling, renting or other types of contracts. These technologies also entered many realms, such as competitions, games, advertisements, and marketing. Many of the users of these technologies fell into Islamic legal prohibitions, such as interest, ambiguity, cheating, and other matters; whether this was done with knowledge or without knowledge. This study aims to clarify some of the rulings related to mobile phone and its technologies, and to show the Islamic rulings of many of the financial contracts that are conducted through these technologies. The researcher relied on the analytical descriptive method to clarify and analyse the views and opinions of the scholars on the subject matter, taking into consideration the recognized four schools of Jurisprudence when deriving the rulings of these issues, relying on traditional sources whenever possible. The study concluded several results, most importantly, that what is intended with mobile technologies are the applications (and utilities) which are installed on them from time to time, such as Bluetooth, text messaging, applications and so forth. (It also concludes) that that Islamic law has important principles and maxims which encompass the ruling on countless contemporary issues, such as the default ruling of permissibility (until proven prohibited), there is no harm to be done intentionally or unintentionally, harm is to be uplifted, and other comprehensive legal maxims. It also concludes that a sale contract that takes place using mobile technology is considered an electronic sale, and must follow the requirements and regulation of elactronic sales.It concludes that many financial transactions that are condected through mobile technologies can be classified according to the rulings of the Islamic jurists, whether one is considering the fulfilment of conditions and requirements, or the absence of impermissible matters, or in terms of making an analogy based on hypothetical or actual situations (that have been previously been researched). The study found that there are many important differences between mobile banking services and traditional banking services. This positively reflects the Islamic ruling regarding banking services conducted over the mobile phone.